Assessment of reactions of diverse maize inbred lines to Striga hermonthica (Del.) Benth - Menkir, A. (Wiley, 2006)
Striga hermonthica is the most widespread and destructive obligate root parasite infecting maize and other cereals in Africa. Maize inbred lines supporting reduced S. hermonthica emergence can form an important basis for developing Striga‐resistant maize cultivars. Twenty new inbred lines selected for field resistance to S. hermonthica, and five inbred checks with known resitance, tolerance and susceptibility reactions to S. hermonthica were evaluated in pots, greenhouse and field experiments under artificial Striga infestation for 3 years. The experiments were conducted to determine the extent of variation in parasite attachment to the roots of these lines and its relationship with emerged Striga plants and other traits. Significant differences (P < 0.0001) were detected among the inbred lines for the numbers of attached and emerged Striga plants and the results were consistent across test environments. Also, the lines exhibited significant differences for Striga damage symptom ratings and other traits recorded in the field. Parasite attachment to the roots was significantly correlated with emerged Striga count in the screenhouse (r = 0.67–0.68, P < 0.001) and in the field (r = 0.82–0.84, P < 0.0001) and with levels of grain yield reduction due to Striga (r = 0.71, P < 0.0001). Regression analysis of the numbers of attached parasites on the first principal component axis scores that integrated several traits recorded in the field was significant (P < 0.0001) and accounted for 62% of the total variation in numbers of attached parasites. The new inbred lines and the resistant inbred check were the least affected by S. hermonthica and exhibited yield losses of 0–37% compared with the yields of the tolerant and the susceptible inbred checks, which were reduced by 40–85%. Sixteen new inbred lines supported significantly fewer attached parasites compared with the susceptible inbred check. Some of these lines also supported significantly fewer emerged parasites and sustained lower damage symptoms and percentage yield losses due to Striga compared with the susceptible inbred check. These inbred lines would be useful in breeding programmes for developing resistant maize cultivars.